Struktur Naratif Lakon Kresna Duta Versi Ki Nartosabdo - Endah Budiarti (Institut Seni Indonesia Yogyakarta, 2021)
AbstractThis research aims to find the narrative structure of Ki Nartosabdo’s version of Kresna Duta. Research data in the form of cassette tape recordings. Vladimir Propp’s fabled structure theory was adapted in this study. Propp theory says that a fairy tale has a structure formed from functions that move sequentially. Related to the theory, the analysis method used is the structural method of the Propp model. The first strategy is to track the events that occur in each scene in the text of Ki Nartosabdo’s version of Kresna Duta. From these events found dramatic personae (hero) in the event and how the hero’s actions in moving the story. From the tracking of this event revealed what actions of the hero present, and also revealed the sequence of actions of the hero. The disclosure of the hero’s actions (functions) and the sequence of actions of the hero (function), it will also be revealed the scheme of movement of the story. There are several things that can be stated from the results of the analysis of The Lakon Kresna Duta version of Ki Nartosabdo. First, thirteen functions (hero actions) were found that were tracked from kresna’s action stream as a hero. Second, Ki Nartosabdo’s version of Kresna Duta has more than one sequence of functions. In this study it is called the sequence of primary actor functions and the sequence of secondary actor functions. The sequence of the primary actor function is the flow of hero actions (Kresna) in the Ki Nartosabdo version of Lakon Kresna Duta, while the secondary actor function is the hero action flow from the previous play or continuation play. Third, Ki Nartosabdo’s version of Lakon Kresna Duta contains one main story movement and four story movements from other plays. A fairly important finding is that Propp’s theory of the narrative structure of folklore (Russia) also applies to Javanese folklore, although there is a deviation in terms of the order of functions.Abstrak Penelitian ini bertujuan menemukan struktur naratif Lakon Kresna Duta versi Ki Nartosabdo. Data penelitian berupa rekaman pita kaset. Teori struktur dongeng Vladimir Propp diadaptasi dalam penelitian ini. Teori Propp mengatakan bahwa sebuah dongeng memiliki struktur yang dibentuk dari fungsi-fungsi yang bergerak berurutan. Berkaitan dengan teori tersebut, maka metode analisis yang digunakan adalah metode struktural model Propp. Strategi pertama yang dilakukan yaitu melacak peristiwa-peristiwa yang terjadi pada setiap adegan dalam teks Lakon Kresna Duta versi Ki Nartosabdo. Dari peristiwa-peristiwa tersebut ditemukan siapa pelaku (dramatis personae) dalam peristiwa tersebut dan bagaimana tindakan pelaku dalam menggerakkan cerita. Dari pelacakan peristiwa ini terungkap apa saja tindakan pelaku yang hadir, dan juga terungkap urutan tindakan pelaku. Terungkapnya tindakan pelaku (fungsi) dan urutan tindakan pelaku (fungsi), maka akan terungkap pula skema pergerakan cerita. Ada beberapa hal yang dapat dikemukakan dari hasil analisis Lakon Kresna Duta versi Ki Nartosabdo. Pertama, ditemukan tiga belas fungsi (tindakan hero) yang dilacak dari aliran tindakan Kresna sebagai hero. Kedua, Lakon Kresna Duta versi Ki Nartosabdo memiliki lebih dari satu urutan fungsi. Dalam penelitian ini disebut urutan fungsi pelaku primer dan urutan fungsi pelaku sekunder. Urutan fungsi pelaku primer merupakan aliran tindakan hero (Kresna) dalam Lakon Kresna Duta versi Ki Nartosabdo, sedangkan fungsi pelaku sekunder merupakan aliran tindakan hero dari lakon sebelumnya atau lakon kelanjutannya. Ketiga, Lakon Kresna Duta versi Ki Nartosabdo ini memuat satu pergerakan cerita utama dan empat pergerakan cerita dari lakon lain. Temuan yang cukup penting ialah teori Propp tentang struktur naratif cerita rakyat (Rusia) juga berlaku untuk cerita rakyat Jawa, meskipun ada deviasi dalam hal urutan fungsi.